IMPLEMENTASI PELAYANAN BPJS KESEHATAN DI RUMAH SAKIT MARTHEN INDEY KOTA JAYAPURA - Sabru, Simon; Silo, Akbar; Aedah, Nur (JURNAL KEBIJAKAN PUBLIK, 2024)
The health insurance policy organized by the Health Social Security Organizing Agency (BPJS) based on Presidential Regulation No. 28 Article 1 of 2018 aims to provide all Indonesian people with a great opportunity to protect their health better. This study aims to analyze the health insurance policy (BPJS) at Marthen Indey Hospital, Jayapura City and to find out the inhibiting factors and supporting factors in the implementation of the policy. This research is important to improve the implementation of the BPJS Health policy at Marthen Indey Hospital to support the development of quality health services. The approach used is a qualitative approach method, with data collection techniques, namely by means of field studies with interviews and observations. Analysis includes the stages of reduction, presentation, and conclusion drawing. The results showed that the implementation of BPJS Health services at Marthen Indey Hospital went well with the support of effective communication, competent human resources, and service digitalization, despite facing obstacles such as limited facilities, lack of understanding of participants, and network problems. To overcome these obstacles, the hospital seeks to increase socialization, improve digital infrastructure, and optimize claims management to ensure more efficient and satisfying services.